RuBi-Glutamate: Two-photon and visible-light photoactivation of neurons and dendritic spines - Fino, Elodie; Araya, Roberto; Peterka, Darcy S.; Salierno, Marcelo; Etchenique, Roberto; Yuste, Rafael (Frontiers in Neural Circuits, 2009)
We describe neurobiological applications of RuBi-Glutamate, a novel caged-glutamate compound based on ruthenium photochemistry. RuBi-Glutamate can be excited with visible wavelengths and releases glutamate after one- or two-photon excitation. It has high quantum efficiency and can be used at low concentrations, partly avoiding the blockade of GABAergic transmission present with other caged compounds. Two-photon uncaging of RuBi-glutamate has a high spatial resolution and generates excitatory responses in individual dendritic spines with physiological kinetics. With laser beam multiplexing, RuBi-Glutamate uncaging can also be used to depolarize and fire pyramidal neurons with single-cell resolution. RuBi-Glutamate therefore enables the photo-activation of neuronal dendrites and circuits with visible or two-photon light sources, achieving single spine, or single cell, precision.